The first report of rabies in stone marten (Martes foina) in Chaharmahal and Bakhtiari Province (Iran) - Seyed Hossein Zamzam; Mohammadreza Ghorani; Fahime Eslami; Saeed Mostofi (Veterinary Medicine and Science, 2024)
Abstract Rabies is a prevalent endemic and zoonotic fatal disease, which is normally transmitted to humans by contact (scratches and bites) from infected animals. The present paper deals with the first documented evidence of rabies in the stone marten (Martes foina). Rabies symptoms were observed in a marten in Chaharmahal and Bakhtiari province. The animal with a strange demeanour approached people without fear, which was died after some while. Samples were taken from its brain (cerebellum, hippocampus, and hypothalamus), shortly after death. In this report, laboratory evidence of rabies by fluorescent antibody (FAT) was proved. The present work is valuable because of the environmental importance of the stone marten. Hence, sensitive surveillance and advanced reporting systems should be regularly monitored on suspected cases of rabies in animals and humans to control and prevent this deadly disease. This involves exposure history, clinical examinations, symptoms and experimental results. Rabies can be controlled by fast diagnostic tests and vaccination.